(untitled) (REMUNOM, 2024)
The 1988 Federal Constitution provides in its 5th article the fundamental rights of every Brazilian citizen. However, this same institute informs that these rights are not absolute, that is, they have limitations, from the moment that one fundamental right limits the other. In this article, freedom of expression is being addressed, which is limited from the moment the dissemination of information proposed by a certain individual comes to harm the subjective honor of another. Therefore, there is a violation of the dignity of the human person. Furthermore, methodologically, it relates the legal, doctrinal and jurisprudential institutes to the concept of fundamental rights studied, aiming at a better understanding of the problems existing in the limitation of a fundamental right from the moment it violates another. Finally, it highlights the relevance of taking these institutes to school environments and the importance of taking care to justify the limits of fundamental rights.